The effect of electron beam treatment on hydrogen sorption ability of commercially pure titanium; Applied Surface Science; Vol. 284 - Panin A. V. Alexey Viktorovich; Kazachenok M. S. Marina S.; Kretova O. M. Oksana M.; Perevalova O. B. Olga B.; Ivanov Yu. F. Yurii F.; Lider A. M. Andrey Markovich; Stepanova O. M. Olga Mikhailovna; Kroening H. M. V. A. Hans Michael Wilhelm Adolf (2013, 2013)
Title screen